The Impact of Family Functioning on Self-Esteem and Resilience Among Young Adults in the Southern Region of Bangladesh - Sultana, Momtaz; Sharmin, Nusrat; Kabir, Sanjida; Thakur, Protiva (Dhaka University Journal of Biological Sciences, 2024)
Family functioning, such as family adaptability and family cohesion, is a crucial component of every individual’s life, can influence his/her self-esteem and resilience, acting as protective factors in the environment. The present study examined the impact of family functioning on self-esteem and resilience among university students in the southern region of Bangladesh. A cross-sectional survey was carried out on 400 students from four different universities situated at Gopalganj, Khulna, Barisal, and Jessore. Bangla version of Resilience Scale for Adults, Rosenberg Self Esteem Scale, Family Adaptability and Cohesion Scale II, and Personal Information Form were used for data collection. Independent sample ‘t’ test revealed significant gender differences in family functioning; Pearson’s correlation coefficient showed significant positive relationship among family functioning, self-esteem and resilience; regression analysis showed both self-esteem and resilience can be predicted by family functioning. The results can inform efforts to strengthen family relationships and enhance communication within families. Dhaka Univ. J. Biol. Sci. 33(2): 87-95, 2024 (July)